The factor that contributed on perceived fairness in performance appraisal in care Ion Technoligist Sdn Bhd Kerteh / Siti Safura Muhamad Mustafa - Muhamad Mustafa, Siti Safura (2014)
The topic is about a study on the factor that contributed on perceived fairness in performance appraisal among employees. The researcher has decided some dependant variables and also independent variables. The researcher dependant variable is the Fairness in Performance Appraisal. Justice in Procedural, Distributive justice and Interactional justice will be independent variables. The researcher will conduct research based on the factor that contributed independent variable on dependant variable.